Age as a determinant of nutritional status: A cross sectional study - Sarah Förster; Salah Gariballa (2005)
Abstract Background Undenutrition is known to be prevalent and largely unrecognised in older patients; however, aberrations in indicators of nutritional status may simply reflect effects of age and/or functional disability. Objective The aim of this study was to measure the effect, if any of age on nutritional status in older patients. Design 445 randomly selected hospitalised patients consented to nutritional status assessment derived from anthropometric, haematological, and biochemical data within 72 hours of admission. Nutritional status was compared between those age < 75 years and those aged 75 years or more. Using multiple regression models, we measured the association between age and nutritional assessment variables after adjusting for disability, chronic illness, medications, smoking and tissue inflammation. Results Body weight, body mass index, mid-upper arm circumference, haemoglobin, serum albumin and plasma ascorbic acid were all significantly lower in people aged ≥ 75 years compared with those < 75 years of age. Although riboflavin (vitamin B2), 25OH VitD 3 , red-cell folate and vitamin B 12 concentrations were lower in those aged ≥ 75 years, differences were not statistically significant. After adjusting for disability and co-morbidity in a multivariate analysis, age alone had a significant and independent effect on important anthropometric and biochemical nutritional assessment variables. Conclusion Increasing age is independently associated with poor nutritional status. This may partly explain the poor clinical outcome in older patients.